Characterization of a Halostable Metalloprotease from the Halophilic Bacterium Bacillus clausii J1G-0%B - Annisa Dila Febriyanti; Mukhammad Asy'ari (Jurnal Kimia Sains dan Aplikasi, 2024)
Protein plays a crucial role as a biocatalyst in various industries, particularly in breaking down proteins into amino acids. The demand for proteases capable of functioning under extreme conditions, such as high salinity, temperature, and pH, is increasing. To address this, the exploration of bacteria that produce stable proteases in such environments is essential. Bacillus clausii J1G-0%B, a halophilic bacterium isolated from Madura salt ponds, thrives in salinity levels of 0-20% NaCl. This study aims to obtain and characterize the protease produced by Bacillus clausii J1G-0%B, focusing on its activity and stability under extreme conditions. The research involved screening, production, and purification of the protease using ammonium sulfate fractionation and dialysis. Protease activity was measured using the Kunitz method, and protein content was determined using the Lowry method. Characterization included optimizing enzymatic conditions (pH, temperature, NaCl concentration), identifying metalloprotease types, and analyzing enzyme kinetics and thermodynamics. The study successfully produced protease using a halophilic medium with casein and 5% NaCl. After 96 hours of incubation, the protease exhibited a specific activity of 654.737 U/mg. Optimal activity was observed at pH 7, 50°C, and 10% NaCl, with stability between 2.5% and 15% NaCl concentration. Enzyme kinetics revealed a high affinity for casein, with a KM value of 0.164 mg/mL and Vmax of 13.182 µmol/mL·min. Thermodynamic analysis indicated high stability, as shown by a positive ΔGi value (+105.84 kJ/mol), a low inactivation constant (ki = 0.0031 min-1), and a long half-life (t½ = 223.548 minutes). EDTA chelation tests confirmed that the protease is a metalloprotease. The halostable protease from Bacillus clausii J1G-0%B shows significant potential for industrial applications and bioremediation in high-salinity environments.